Contact and Fumigant Toxicity of Essential Oils Against Callosobruchus maculatus (University Journal of Zoology, Rajshahi University, 2008)
Toxicity of five essential oils (EOs), viz. cardamom, cinnamon, clove, eucalyptus and neem oils were investigated against the cowpea weevil, Callosobruchus maculates (Fab.) adults, through contact and fumigation bioassay. In the contact bioassay eucalyptus oil was found to be the most effective in inducing mortality both after 24 and 48 h of treatments. The toxicity of the oils followed in the order: eucalyptus > clove > cinnamon > cardamom > neem. In the fumigation bioassay, however, a reverse result was obtained with eucalyptus oil where it shows the last position for 24 h and fourth position for 48 h after treatments. The efficacy in respect of the toxicity followed in the order: clove > cinnamon > cardamom > neem > eucalyptus after 24 h after treatment, and clove > cinnamon > cardamom > eucalyptus > neem after 48 h after treatments. Keywords: Essential oil, bioassay, LD50, C. maculates Univ. j. zool. Rajshahi Univ. Vol. 26, 2007. pp. 63-66